2005
DOI: 10.1126/science.1113207
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Hard-Sphere Crystal Growth Frustrated by Large Spherical Impurities

Abstract: Impurities affect the nucleation, growth, and structure of crystals. Here we report the effect of large, spherical, polymethylmethacrylate impurities on the crystal growth of monodisperse, hard, polymethylmethacrylate colloids in a density- and optically matching apolar solvent mixture. Crystal growth, initiated at the bottom of the sample, was studied by imaging sequences of two-dimensional xy slices in the plane of the impurity's center with a laser scanning confocal microscope. Impurities form the center of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 18 publications
3
107
0
Order By: Relevance
“…The increase in the number of smaller particles (< 10 nm) may be attributed to the suppression of particle growth by the introduction of Cu atoms into the TiO 2 crystal structure. De Villeneuve et al (2005) reported that impurities could influence the nucleation, growth, and structure of crystals. Kubota (2001) also addressed that crystal growth is markedly affected by the impurities presented in the system.…”
Section: Characteristics Of Cu-doped Tio 2 Nanoparticlesmentioning
confidence: 99%
“…The increase in the number of smaller particles (< 10 nm) may be attributed to the suppression of particle growth by the introduction of Cu atoms into the TiO 2 crystal structure. De Villeneuve et al (2005) reported that impurities could influence the nucleation, growth, and structure of crystals. Kubota (2001) also addressed that crystal growth is markedly affected by the impurities presented in the system.…”
Section: Characteristics Of Cu-doped Tio 2 Nanoparticlesmentioning
confidence: 99%
“…Here foreign particles are located inside colloidal suspensions, acting as seeds for crystallization, giving rise to a heterogeneous nucleation process, which starts on the surface of a curved hard wall (the surface of the foreign particles) 45 . Such studies have also shown how curvature and geometric frustration can modify NG.…”
Section: Modelmentioning
confidence: 99%
“…Already, the simplest conceivable multicomponent system, i.e., a binary mixture of hard spheres, exhibits interesting and complex behavior. Just a few examples include entropy driven formation of binary crystals [1][2][3], frustrated crystal growth [4], the Brazil nut effect [5], glass-formation [6,7], and entropic selectivity in external fields [8]. Although interaction potentials in atomic systems are more complex than those of hard spheres, the principle of volume exclusion is ubiquitous and thus always dominates the short-range order in liquids [9].…”
mentioning
confidence: 99%